Data reassessment in a phylogenetic context gives insight into chromosome evolution in the giant genus Solanum (Solanaceae). Issue 4 (19th May 2018) - Chiarini, Franco; Sazatornil, Federico; Bernardello, Gabriel
Abstract : Chromosome data are fundamental in evolution. However, there has been no attempt to synthesize and evaluate the significance of such information from a phylogenetic perspective in the giant genus Solanum, which was the aim of this work. New and published information of the main cytotaxonomic features (chromosome number, polyploidy, total length of the haploid complement, mean chromosome length, mean arm ratio, karyotype formula, nuclear DNA amount, number/position of rDNA sites) was compiled and mapped onto an embracing Solanaceae phylogeny, performing Ancestral States Reconstruction. There were 506 Solanum species with chromosome counts (49.7% from an estimated total of 1, 018 spp.), with x = 12 being the most frequent number (97%). Species with karyotypes represent 18.8%, while 8% have been studied with any molecular cytogenetic technique. Chromosome characters showed transitions associated with supported nodes, some of which have undergone fewer transitions than others. The common ancestor of all Solanum was a diploid with 2n = 24, a karyotype with st and/or t chromosomes, 2C DNA content of 1–1.2 pg, one locus of 18–5.8–26S rDNA and one of 5S, both loci being asyntenic. The chromosomal variables behave as homoplastic, with reversions in all branches. The analysed characters were sorted from more to less conserved: asynteny of rDNA loci; number of sites of 18–5.8–26S; chromosome number; karyotype formula; number of 5S loci. This pattern of chromosomal evolution distinguishes Solanum from closely related genera and from genera from other families with a similar number of species.